Case Report: Return to Sport Following the COVID-19 Lockdown and Its Impact on Injury Rates in the German Soccer League - Seshadri, Dhruv R.; Thom, Mitchell L.; Harlow, Ethan R.; Drummond, Colin K.; Voos, James E. (Frontiers in Sports and Active Living, 2021)
The COVID-19 pandemic has forced the suspension or delay of sporting leagues and events worldwide, including the elite German soccer league, the Bundesliga. As the Bundesliga made headlines for becoming the first major sports league to return to sport worldwide, many sports scientists have warned of increased injury rates in athletes following home confinement. To-date, there lacks retrospective studies on longitudinal injury rates to elucidate the effect public health isolation measures had on the health and safety of professional athletes. This study sought to compare real-world injury rates experienced by Bundesliga athletes before and after the COVID-19 lockdown. We hypothesized that an increased risk in injury following the lockdown would result in part due to deconditioning (e.g. loss of muscle strength and decrease in fitness levels), high acute workloads from expedited return-to-play (RTP) programs, and more frequent competitive matches. Data was collected from public injury and player reports regarding the Bundesliga. Between the league’s resumption and completion on May 16 and June 27, 2020, a total of 70 injuries occurred over the course of 82 games. 12.6% of all 537 athletes were injured in the 82 games after lockdown, while 11.2% of athletes were injured in the 224 games prior to the lockdown. When normalized to the number of games played for the respective parts of the season, 0.15% of athletes suffered an injury per game post-COVID-19 lockdown than 0.05% of athletes suffering an injury pre-COVID-19 lockdown. 22 forwards, 23 midfielders, 22 defenders, and 2 goalkeepers experienced a 3.1x higher rate of injury per game post-lockdown compared to injury rates pre-lockdown (0.84 injuries per game vs. 0.27 injuries per game). Athletes were 3.1x more likely to be injured returning to play following the COVID-19 lockdown. Current injury rate per game is 0.84 vs 0.27 per game pre-COVID-19. High injury incidence for players yet to complete their first competitive match relative to players who have successfully competed in matches may imply suboptimal sport readiness following home confinement. Athletes did not experience an increased rate of injury with more cumulative competitive matches played.